Literasi Keuangan dan Pendapatan terhadap Keputusan Investasi Mahasiswa dengan Perilaku Keuangan sebagai Variabel Intervening - Khofifah Amalia Sekar Putri; Sari Andayani (IPM2KPE, 2022)
This study aims to determine the effect of financial literacy, income, and financial behavior as intervening variables on investment decisions of active undergraduate students of accounting at UPN